Effects of Mechanized Irrigation Protocols on Endodontic Obturation Using Calcium Silicate-Based Sealer - Galvani, Lucas David [UNESP]; Barros, Antonia Patricia Oliveira [UNESP]; Costa, Joatan Lucas de Sousa Gomes; Oliveira, Eliane Cristina Gulin de [UNESP]; Bordini, Ester Alves Ferreira; Vaz, Luís Geraldo [UNESP]; Kuga, Milton Carlos [UNESP] (MDPI, 2024)
The aim of this study was to evaluate the effects of mechanized final irrigation protocols (XPE, XP-Endo Finisher; XPC, XP-Clean; and ECL, Easy Clean) compared to PUI (passive ultrasonic irrigation) on the debris incidence and open dentinal tubules, and their effects on the adhesion interface after 48 h and 6 months. One hundred twenty maxillary central incisors were submitted to chemical–mechanical preparation using a rotary instrument and 2.5% sodium hypochlorite. Specimens were distributed in 4 groups (n = 30) in accordance with the mechanized final irrigation protocol: XPE, XPC, ECL, or PUI. Forty specimens (n = 10/group) were submitted to SEM analysis to evaluate the residue incidence and dentin open tubules. The other specimens were obturated using Bio-C Sealer and submitted to push-out bond strength and adhesive failure mode evaluations in the cervical, middle, and apical thirds after 48 h or 6 months (n = 10/group). Only in the apical third, ECL presented the highest residue incidence and fewer open dentinal tubules when compared to the XPE, XPC, and PUI groups (p < 0.05). In the cervical and middle root thirds, no significant differences were observed regardless of the group evaluated (p > 0.05). After 48 h, ECL resulted in the lowest bond strength only in the apical third (p < 0.05), while the XPE, XPC, and PUI groups remained similar in the cervical and middle thirds (p > 0.05). At 6 months, all groups showed lower bond strength values regardless of the root third evaluated, but ECL showed the lowest bond strength in the apical and middle root thirds when compared to the other groups (p < 0.05). The ECL protocol did not provide adequate residue removal on the apical radicular third and negatively affected the longevity of endodontic obturation using a calcium silicate-based sealer.
Keywords: calcium silicate; dentin debris; endodontic irrigation; scanning electron microscopy; ultrasonics